Surface-initiated RAFT polymerization of p (MA POSS-co-DMAEMA+) brushes on PDMS for improving antiadhesive and antibacterial properties. Issue 2 (22nd January 2016) - Wang, Bailiang; Jin, Tingwei; Han, Yuemei; Shen, Chenghui; Li, Qing; Tang, Junmei; Chen, Hao; Lin, Quankui
ABSTRACT: Poly (dimethylsiloxane) (PDMS) silicones, as a common intraocular lenses material, often lead to the happen of posterior capsule opacification due to the adhesion and reproduction of residual human lens epithelial cells (HLECs) on the posterior capsule after surgery. Bacterial infection is a potentially catastrophic complication of cataract surgery, which occurs within several days after implantation of the lens. A novel poly (methacrylisobutyl polyhedral oligomeric silsesquioxane- co -2-(dimethylamino)-ethyl methacrylate) (p (MA POSS- co -DMAEMA)) brush was synthesized by reversible addition–fragmentation chain-transfer (RAFT) polymerization. After being quaternized treatment by 1-bromo-heptane, p (MA POSS- co -DMAEMA + ) brushes with bactericidal function were obtained. The optical transmission of the brushes functionalized PDMS was better than p (DMAEMA + ) coating modified PDMS, which may be due to the similar chemical composition of MA POSS and PDMS. Measurements of water contact angle, spectroscopic ellipsometry, and atomic force microscope were used to characterize hydrophilicity, thickness, and morphology of the brushes. Results revealed that brushes rendered PDMS surface more hydrophilicity and higher roughness. Adherences of bovine serum albumin and HLECs on the p (MA POSS- co -DMAEMA + ) brushes were significantly reduced due to the hydrophilic property and cytotoxicity of the brushes. Bactericidal activity of the brushes, measured by shake-flask culture and LIVE/DEAD bacterial viability kit staining methods, was remarkably effective against S. aureus owing to the component of p (DMAEMA + ). GRAPHICAL ABSTRACT: